Landscapes of monastic foundation the establishment of religious houses in East Anglia c. 650-1200 - Pestell, Tim (Anglo-Saxon studies, 2004)
Monastic studies usually focus upon the post-Conquest period; here, in valuable contrast, the focus is on pre-Conquest monastic foundations, in the present-day counties of Norfolk and Suffolk. Tim Pestell considers the place of the monastery in wider landscapes - topographical, social, economic and political. He observes that by 1215 the Diocese of Norwich contained about a tenth of all English monasteries, a remarkable richness of patronage was no sudden flush of enthusiasm, but a manifestation of religious devotion that had been evolving in East Anglia since the seventh-century Conversion. By integrating archaeological and historical sources, Dr Pestell presents an in-depth examination of where and how communal religious life developed in the region over half a millennium. In so doing, he demonstrates how the more visible and better-evidenced post-Conquest monastic landscape was typically structured by its Anglo-Saxon past. Dr TIM PESTELL is Curator of Archaeology at Norwich Castle Museum